(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In modern state educational policy, the priority of the personality of the subject and object of education is proclaimed; criteria of the modern personality are formed, among which the most important are spirituality, comprehensive development, healthy interests and needs (especially cognitive, value-oriented, intellectual and creative, self-educational, self-actualization and self-realization).